2004
DOI: 10.1111/j.1398-9995.2004.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Chinese herbal medicine in the treatment of patients with seasonal allergic rhinitis: a randomized‐controlled clinical trial

Abstract: The results of this study suggest that traditional Chinese therapy may be an efficacious and safe treatment option for patients with seasonal AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 34 publications
2
66
0
2
Order By: Relevance
“…. In addition to the basic formula, every patient received a second additional formula tailored to his or her individual TCM diagnosis (46).…”
Section: Examplesmentioning
confidence: 99%
“…. In addition to the basic formula, every patient received a second additional formula tailored to his or her individual TCM diagnosis (46).…”
Section: Examplesmentioning
confidence: 99%
“…For instance, one study with a mixture of 18 Chinese herbs showed a significant efficacy of the treatment in seasonal rhinitis (symptoms and QoL) [53], and another the Chinese herb formulation biminne was statistically effective in perennial rhinitis [54]. One recent study using a combination of acupuncture and Chinese herbs found a significant effect on symptom scores and quality of life in seasonal allergic rhinitis [55]. On the other hand, a rigorous double blind randomized controlled trial showed that grapeseed extract was not more effective than placebo for ragweed induced rhinitis [56].…”
Section: Phytotherapymentioning
confidence: 99%
“…(iii) Chinese herbal medicine was to be taken three times per day over a period of 6 weeks and parallel to acupuncture treatment… All herbs used in the present study were imported from China by a single TCM herbal medicine import company (Sinores, Lueneberg, Germany)… All herbs were prepared in dried, minced pieces and then sealed in generic paper sachets by a pharmacist in order to render the herbal formulation non-identifiable for patients… In addition to the basic formula, every patient received a second additional formula tailored to his or her individual TCM diagnosis [46].…”
Section: Item 4amentioning
confidence: 99%